Adult daughters' reflections on their affective experiences growing up with a psychotic mother: a psychodynamic exploration - Govinda, Nishara (My University, 2015)
The aim of the research was to investigate adult daughters’ retrospective accounts of experiences with their mothers with reference to their emotional or affective experiences. The second aim of the research was to explore these daughters’ views of how their experiences have impacted their day-to-day lives, including how they relate to significant others in their lives, such as life partners and their own children. Four adult daughters who were raised by psychotic mothers were interviewed, using a semi-structured interview schedule. Through the process of Interpretive Phenomenological Analysis, six themes and nine subthemes emerged from the data. The themes that emerged from the data included: (1) ‘Present nature of the mother daughter relationship’; (2) ‘Adapting/coping’, comprising of three subthemes; ‘Support’, ‘Escaping’ and ‘Psychological boundaries’; (3) ‘Perceived impact of past’, which comprises of three subthemes, ‘Perceived impact on life’, ‘Perceived impact on sense of self’ and ‘Taking responsibility’; (4) ‘Fear’ the fears that resulted from participant’s experiences of growing up with their psychotic mothers; (5) ‘Secrecy and stigma’; (6) ‘What to say to another daughter’ which comprises of three subthemes, ‘Support’, ‘Coping’, ‘Professional services’. Powerful overwhelming feelings were notably expressed through the participants’ narrative, including guilt, shame, fear, anxiety, disappointment and confusion. The means through which these children managed their powerful feelings, has indeed left a prevailing impact on their sense of selves as well as their lives. Some of the powerful feelings that daughters raised as currently experiencing in relation to their psychotic mothers include anger, disappointment, sadness, guilt, shame, loyalty and resignation. The findings of the research were interpreted using a psychodynamic framework. The psychodynamic findings were that participants remember experiencing strong overwhelming feelings that they had to manage themselves in response to a failure in the reciprocity with their relationships with their psychotic mothers (Klein, 1926; 1935; 1940; 1946; 1956). They emphasised the necessity of having a parental figure who could contain their overwhelming feelings (Bion, 1959; 1962; 1963; 1967; 1993). Furthermore, participants highlighted having had to adapt themselves in order to meet the needs of their environment, culminating in the development of the self (Winnicott, 1960a; 1960b; 1963; 1965).
A thesis submitted to the faculty of Arts of The University of The Witwatersrand, in partial fulfilment of the Masters Degree in Clinical Psychology, Johannesburg, 7 January 2015